Operative conditions evaluation for efficient building retrofit : a case study - Silva, Sandra Monteiro (2013)
The implementation of energy efficiency measures into the existing building stock is essential to meet the 2020 targets set by the EU Energy Performance of Buildings Directive (EPBD) and reinforced with the "EPBD-recast". Thus, energy refurbishment of existing buildings is fundamental to achieve these goals. However, energy issues should not be the only concerns since the indoor environmental quality (IEQ) is also as important. When planning a building retrofit it is then necessary to consider the energy efficiency requirements as well as the IEQ. To do so, the main problems of the existing buildings should be identified. This work presents a study carried out in a large office building to identify the main pathologies related to the energy efficiency and to the IEQ. The main objective of this study was to characterize the actual situation of a building that represents a great number of the Portuguese office buildings in order to identify the principal problems that occurs in this type of buildings, to support the development of a refurbishment project of the building that can optimize both the energy efficiency and the relevant parameters to the IEQ and that are also solutions with potential to be used in other buildings.